2021
DOI: 10.1039/d1qi00781e
|View full text |Cite
|
Sign up to set email alerts
|

A new family of Fe4Ln4 (Ln = DyIII, GdIII, YIII) wheel type complexes with ferromagnetic interaction, magnetocaloric effect and zero-field SMM behavior

Abstract: In this work, we report three isostructural Fe4Ln4 wheel type complexes with molecular formula [{Fe4(dea)4Dy4(deaH)8(µ2-OMe)4}(NO3)4]·4(H2O) (1), [{Fe4(dea)4Gd4(deaH)8(µ2-OMe)4}‧(NO3)4]·4(H2O)·4(MeOH) (2) and [{Fe4(dea)4Y4(deaH)8(µ2-OMe)4}(NO3)4]·4(H2O)·6(MeOH) (3), (where dea = diethanolamine). Detailed structural analysis disclose that...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 100 publications
0
10
0
Order By: Relevance
“…Single-molecule magnet (SMM) and magnetocaloric effect (MCE), inter alia , are the two most important lanthanide-magnetism topics that have tantalized the attention of both chemists and physicists in recent years. The Dy 3+ compounds, because of their significant anisotropy arising from large unquenched orbital angular momentum and a high energy reversal barrier, more-often-than-not show slow magnetic relaxation and dominate SMM studies. On the other hand, the Gd 3+ ion, by virtue of its large spin-only magnetic moment, weak superexchange interaction, and quenched orbital momentum, predominates the recent quest for low-cost, environmentally benign cryogenic technology using MCE-based magnetic refrigeration. Notwithstanding their individual magnetic features, the combination of Dy 3+ and Gd 3+ with transition metals is often found to excel the magnetic behavior. …”
Section: Introductionmentioning
confidence: 99%
“…Single-molecule magnet (SMM) and magnetocaloric effect (MCE), inter alia , are the two most important lanthanide-magnetism topics that have tantalized the attention of both chemists and physicists in recent years. The Dy 3+ compounds, because of their significant anisotropy arising from large unquenched orbital angular momentum and a high energy reversal barrier, more-often-than-not show slow magnetic relaxation and dominate SMM studies. On the other hand, the Gd 3+ ion, by virtue of its large spin-only magnetic moment, weak superexchange interaction, and quenched orbital momentum, predominates the recent quest for low-cost, environmentally benign cryogenic technology using MCE-based magnetic refrigeration. Notwithstanding their individual magnetic features, the combination of Dy 3+ and Gd 3+ with transition metals is often found to excel the magnetic behavior. …”
Section: Introductionmentioning
confidence: 99%
“…As we know, 4f metal ions are more attracted to hard atoms such as O and F, while 3d ions are likely to bind soft atoms such as N and S according to the hard–soft acid–base principle . Thus, previously established methodologies for mixed 3d-4f metal rings are of great importance to synthesize Sc–Gd heterometallic rings. We found that it is necessary to reduce the amount of base for the synthesis of smaller rings compared with the larger ones. In fact, the H 2 mdea ligands are fully deprotonated in Sc 8 Gd 8 and Sc 6 Gd 6, while in Sc 4 Gd 4 , there are two H 2 mdea ligands that are not fully deprotonated, in which only one proton is removed.…”
Section: Resultsmentioning
confidence: 99%
“…However, by comparing the magnetic data and the behavior of 1 and 2, it is found that the initial decrease of the χ m T products on cooling of 2 is due to the depopulation of the Stark levels of the Dy III ion. 50 In addition, the increase of the χ m T products below 44 K is due to the ferromagnetic coupling between the Co II ions in 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%